IMPLEMENTASI PERDA NO. 11 TAHUN 2011 TENTANG PAJAK BUMI DAN BANGUNAN DESA PANCURAN GADING KECAMATAN TAPUNG KABUPATEN KAMPAR - Thia Lestari; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Regional autonomy is a form of delegation of authority from central government to local government. One form of regional autonomy that is the transfer of the management of land and building tax Rural and Urban Development (PBB-P2). Kampar district receives delegation of PBB - P2 in 2012 by issuing a Regional Regulation number 11 of 2011 About Tax on Land and Building Rural and Urban . The Purpose of this research was to describe the implementation of the Regional Regulation number 11 of 2011 About Tax on Land and Building Rural and Urban. This type of research is descriptive qualitative method. Subjects in this study was employes DPPKA Kampar, head village and taxpayer. Data retrieved by using semi-structured interviews, observation frankly, documentation, and triangulation techniques. Based on theory of Van Horn Van Matter consisting of size and policy objectives , resources , implementing agent characteristics , attitudes implementing , managing communications between organizations and activities as well as the economic, social and political . Implementation of PBB-P2 in Kampar DPPKA has met six of these variables although there are still some shortcomings such as socialization is done only through banners , village heads and radio , many taxpayers still have to pay awareness of PBB-P2 low and external environmental influences that hinder the implementation of PBB-P2 .Keywords: Implentation policy, property taxes in rural and urban